Valentyna Kalko: LANGUAGE GAME IN UKRAINIAN ANTI-PROVERBS - KALKO, V.V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Abstract. Introduction. Over the course of the years, the attention of the researchers have been attracted to the concept of “game”, its place in human activity, as well as the position of language games and linguistic and creative word-formation. In the context of these studies, much attention is paid to the development and study of such an important and multifaceted phenomenon as a language game, the functioning of which in the language is closely linked with the linguistic and extra linguistic characteristics of the speaker and the parameters of the communicative situation. The purpose of the article is to describe the phenomenon of language play as one of the expressive methods of creating аnti-proverbs, which is a marker of anthropocentrism of language, a manifestation of linguistic creativity, communicative and pragmatic potential of language signs. Results. The language game is comprehensively presented and characterized as a complex multidimensional linguistic phenomenon endowed with special semantic and linguistic and cultural characteristics. Аnti-proverbs are treated as such, in the form of games are relevant to modern society realities, especially the problem of government, personal choice, formation civil society, interpersonal relationships, and so on. The precedent statements are identified that illustrate the wide variety of authors’ experiment with language material. Originality. The language game is classified in terms of the semiotic approach. The language game with semantic mechanism and the language game with syntactic one were distinguished. At the same time, pragmatics can be found in both semantic and syntactic types of the language game. Using the language game as a creative, non-standard use of a classic proverb, the author seems to create a multilevel text, enhances genre and stylistic syncretism, forms additional content aimed at the addresse’’s interpretive ability to actualize several meanings. Conclusions. The use of anti-proverbs in the text contributes to the expression of the material, strengthening its influence, persuasiveness, argumentation, suggestiveness. Language play as a means of generating аnti-proverbs is a product of linguvo-creative thinking as an individual’s ability to creatively transform language material. It realizes a specific communicative goal due to a programmed violation of a typical language scheme and a conscious deviation from the language norm